On The History Of Odishi-Abkhazian Relatios : (Analysis of One Newly Discovered Important Archival Document) - Kvashilava, Kakha (Actual Problems of Kartvelology, 2025)
Special researches concerning the history of political relations between two Georgian feudal political units – Odishi and Abkhazia in the late mid-centuries have been more or less successful in Georgian historiography. There is no doubt that historical sources and documents referring to the topics of research are materials of great importance. As the lack of these materials is noticeable, the work in the direction of obtaining new documents is highly encouraged. One of the most problematic issues in the Odishi-Abkhazian relations is Samurzakano. Samurzakano, as a separate feudal domain run by the lateral branch of Abkhazian principality, was formed between XVII and XVIII centuries. The document discovered in the Georgian National Centre of Manuscripts in spring 2010 is a very important material in this respect and it has been widely applied in the scientific circles. This is Giorgi (Sapar-Bey) Sharvashidze’s letter addressed to Georgian civic governor general Al. Veliaminovi. The letter is signed by Giorgi Sharvashidze and is dated July 10, 1820 (old style). It is clearly stated in the letter that Saparbey recognized Samegrelo as the possession of Dadiani dynasty. Thus, the manuscript discovered by us is a document of great importance in research of Odishi-Abkhazian relations and the history of Samursakano. The letter confirms existence of Dadiani jurisdiction in this region, which has constantly been disacknowledged by our Abkhazian colleagues on the basis of forged historical sources